Settlement model of waste soil for dumping area in Malaysia - Pauzi N.I.M.; Omar H.; Huat B.K.; Misran H. (2023)
This paper attempted to review previous works on the settlement models of waste soil prediction using constitutive model for open dumping. In Malaysia, open dumping was generally mistaken as landfill. The waste area could be categorized as landfill if the wastes are properly maintained with leachate and gas circulations. The debate of this issue has become the main reason in studying the settlement model of open dumping. The settlement of soil in open dumping could pose serious hazardous effect to human and environment if the areas are to be reclaimed for other construction purposes. Thus, this study is considered a very important subject to be developed. There are four groups of published settlement models of municipal solid waste namely soil mechanic based model, empirical model, rheological model and settlement models which incorporated biodegradation. These models are reviewed and analyzed so as to decide which model is the best suited to be used for open dumping waste in Malaysian scenario. The future trends of this research development could also be predicted based on this paper. 2010 ejge.